Dancing monkeys in Serbian and Korean – exhaustivity requirements on distributive share markers. Issue 1 (29th July 2020) - Bosnić, Ana; Spenader, Jennifer; Demirdache, Hamida
Abstract : In some languages, distributive markers/quantifiers can attach to the argument that is being distributed (the distributive share), as opposed to the restrictor of the sentence (the distributive key). Researchers agree that distributive share markers can also distribute over events (and not only individuals), but disagree as to what these markers are semantically – universal distributive quantifiers or event plurality (pluractional) markers. In this paper, we experimentally probe spatial event distribution. On a universal quantification account, exhaustive distribution over a spatial distributive key is enforced, while on the pluractional analysis there is no such requirement. We carried out two picture verification experiments to test exhaustivity requirements in intransitive sentences with distributive share markers from two typologically different languages: the Serbian marker po and the Korean marker - ssik . We found evidence for an exhaustivity requirement over pluralities of non-atomic individuals (groups), but not over designated spatial locations. We interpret these findings as evidence that the semantics of (spatial) event distribution with distributive share markers involves a (spatial) distributive key. Specifically, po/-ssik have a universal quantificational force (with a meaning akin to per ( each )) establishing a distributive relation between individual events and elements of the spatial distributive key. Plural individuals made salient in the visual input can serve to divide up the spatial key into chunks of space that have to be exhausted.